A Rare Case of an Artery Passing through the Median Perforating Canal of the Mandible - Joe Iwanaga; Koichi Watanabe; Tsuyoshi Saga; Yoko Tabira; Koh-ichi Yamaki (Case Reports in Dentistry)
Along with the popularization of dental implant surgery, there has been considerable research on the lingual foramen using cone-beam computed tomography. Anatomical research has also revealed that the arteries entering the lingual foramina are branches of the submental and sublingual arteries. There have been no reports, however, of the submental or sublingual artery entering the mandible from the lingual foramen, perforating it, and then distributing to the inferior labial region. A 69-year-old man who donated his body to our department in 2015 was dissected. The mandible with overlying soft tissue of the mental region was resected and examined with microcomputed tomography, which showed that the canal perforated from the lingual foramen to the midline of the labial cortical plate. The canal was thus named the median perforating canal. To the best of our knowledge, there have been no other reports of a perforating artery of the mandible, so this case is thought to be rare. Hence, the existence of perforating arteries, such as in the present case, should be taken into consideration in preoperative diagnoses such as for dental implant surgery. Thus, the fusion of anatomical and radiological study is useful and necessary to understand surgical anatomy.